2017
DOI: 10.1038/s41598-017-15792-w
|View full text |Cite|
|
Sign up to set email alerts
|

Dispersion of TiO2 nanoparticles improves burn wound healing and tissue regeneration through specific interaction with blood serum proteins

Abstract: Burn wounds are one of the most important causes of mortality and especially morbidity around the world. Burn wound healing and skin tissue regeneration remain thus one of the most important challenges facing the mankind. In the present study we have addressed this challenge, applying a solution-stabilized dispersion TiO 2 nanoparticles, hypothesizing that their ability to adsorb proteins will render them a strong capacity in inducing body fluid coagulation and create a protective hybrid material coating. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…The ability of TiO 2 nanoparticles in prove reactive oxygen species (ROS) and increase membrane permeability maximize antibacterial activity and improve the wound healing as was observed previously (Sankar et al, 2014). Moreover, the TiO 2 nanoparticles could cause enhanced blood coagulation, which is an important first step in the wound healing process (Seisenbaeva et al, 2017). Our in vivo results were (Figures 4-6) similar to Seisenbaeva et al (2017) and in the study, it was observed that TiO 2 improved wound healing.…”
Section: Figure 5 | (A)supporting
confidence: 85%
See 1 more Smart Citation
“…The ability of TiO 2 nanoparticles in prove reactive oxygen species (ROS) and increase membrane permeability maximize antibacterial activity and improve the wound healing as was observed previously (Sankar et al, 2014). Moreover, the TiO 2 nanoparticles could cause enhanced blood coagulation, which is an important first step in the wound healing process (Seisenbaeva et al, 2017). Our in vivo results were (Figures 4-6) similar to Seisenbaeva et al (2017) and in the study, it was observed that TiO 2 improved wound healing.…”
Section: Figure 5 | (A)supporting
confidence: 85%
“…Moreover, the TiO 2 nanoparticles could cause enhanced blood coagulation, which is an important first step in the wound healing process (Seisenbaeva et al, 2017). Our in vivo results were (Figures 4-6) similar to Seisenbaeva et al (2017) and in the study, it was observed that TiO 2 improved wound healing. We confirmed that the electrospun membranes with TiO 2 can stimulate and modulate inflammation, which is very important for human health, since there is bigger formation of blood vessels (Babelova et al, 2009;Moreth et al, 2014).…”
Section: Figure 5 | (A)supporting
confidence: 81%
“…Adapted from Ref. [214] with permission from the Springer Nature 1 3 vascularization and increased fibrosis hypodermis) have been investigated for rats in the group 3 without the treatment. However, a daily base treatment using TiO 2 nanoparticles for rats in group 4 brought obvious wound-healing effects by thickening epithelium layer, reducing dermal thickness, as well as increasing the formation of new blood vessels and base materials [214].…”
Section: Tissue Regeneration and Chronic Wound Healingmentioning
confidence: 99%
“…TiO 2 NP wound treatment enhances body fluid coagulation by making interaction with blood proteins. The formation of adherent crust of a nanocomposite improved healing of wound and inhibited infection and inflammation [75].…”
Section: Wound Healing Activitymentioning
confidence: 99%